The transformation of the role of the medical professional: challenges, renewal, and responsibility - Yataco Wilcas, Christian Alexander (2023)
The medical profession, influenced by various historical and contemporary factors, is in constant evolution. Technological advances, social changes, economic factors, and scientific developments have shaped the perception of physicians in society. Ethical self-regulation, along with high-quality medical education, is essential for preparing competent and ethical professionals. 21st-century physicians play a crucial role in healthcare, health education, and health promotion. Despite challenges such as monopoly and elitism, it is argued that these do not necessarily diminish the prestige of the profession and can be ethically addressed. Technology has improved medical diagnosis and treatment, as well as telemedicine, but it poses ethical and privacy challenges. Finding a balance between technology and patient-centered care is essential. Likewise, the increase in bureaucracy in healthcare raises concerns about the quality and efficiency of services, but strategies are being implemented to address these issues and maintain patient-centered professionalism. Medicine is a constantly changing discipline that adapts to a dynamic environment while upholding ethical values and the quality of care. The medical profession will evolve with technological and social advances, and it is crucial to preserve ethics and humanity in future medical practice.